A novel TIMM8A mutation in Mohr-Tranebjaerg syndrome without hearing loss and with basal ganglia iron deposition - Ignacio Ventura; Francisco Revert-Ros; Fernando Revert; Jesús Ángel Prieto-Ruiz; José Miguel Hernández-Andreu (Orphanet Journal of Rare Diseases)
Abstract Mohr-Tranebjaerg syndrome (MTS) is a rare X-linked recessive neurodegenerative disorder caused by pathogenic variants in the TIMM8A gene. TIMM8A, also known as Deafness-Dystonia Peptide-1 (DDP1) is a mitochondrial intermembrane space protein involved in the import and insertion of hydrophobic membrane proteins from the cytoplasm into the mitochondrial inner membrane. MTS typically presents early-onset progressive hearing loss, dystonia, visual impairment, and cognitive decline. Here, we report a case of a male adolescent with a previously undescribed variant in TIMM8A, associated with progressive dystonia but no hearing loss, highlighting the clinical variability of MTS. A 16-year-old male was referred for genetic evaluation due to a 6-year history of progressive dystonia, motor coordination difficulties, and iron deposits in the basal ganglia detected by brain MRI. Family history revealed mild motor abnormalities in his maternal uncle and recurrent muscle spasms in his mother. Whole-exome sequencing (WES) identified a c.98_101dupAGCA variant in TIMM8A in hemizygosity, classified as likely pathogenic. This variant causes a frameshift leading to a truncated protein. The patient inherited the variant from his mother, who is heterozygous for the mutation. Although the patient lacks the characteristic early-onset hearing loss seen in MTS, his neurological presentation and the imaging findings are consistent with the syndrome. This case underscores the phenotypic heterogeneity of Mohr-Tranebjaerg syndrome, where patients may present with prominent neurological symptoms such as dystonia without the hallmark auditory dysfunction. The identification of a novel TIMM8A variant expands the mutational spectrum of this rare disorder and provides insights into genotype-phenotype correlations. The absence of hearing loss in this patient raises important questions about the variability in the expression of the mutated TIMM8A. This report highlights a novel TIMM8A mutation associated with Mohr-Tranebjaerg syndrome, presenting primarily with dystonia and iron accumulation in the basal ganglia. The findings contribute to the understanding of the clinical spectrum of MTS and emphasize the importance of genetic testing in patients with unexplained progressive neurological symptoms.